The Art and Politics of Emile Habiby II - Salam Mir (Arab Studies Quarterly, 2015)
In The Secret Life of Saeed, the Pessoptimist , Emile Habiby (1922–1996) addresses the question of Palestinian historiography during the Mandate period through Al-Nakba of 1948 and the second defeat of the Arabs by Israel, in the 1967 June War. Having remained in what became Israel, the Palestinian writer tells the history from the Palestinian perspective and from the “insider's” perspective, to rehabilitate the misperceptions about Arabs and their story. This article will argue that The Pessoptimist , the Palestinian national epic, challenges the mono-vision of the Israeli/Western version that has disseminated myths about what occurred between 1947 and 1948. By inserting into the creative writing the oral history told by Palestinians to their children and grandchildren, and which had failed entry into the official Israeli/western version, Habiby's narrative sets the record straight regarding the labeling of Palestinian resistance fighters as “terrorists.” Constructing a history that refuses to lament, The Pessoptimist voices a distinct Palestinian voice, a dignified identity that claims agency for its own destiny.